New trends in the electronic economy - Polańska, Krystyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2013)
The virtual environment offers a new, dynamic space for running business. All of the business activity occurring on electronic markets can be labelled as the ‘electronic economy’. It does not only comprise the virtual marketplace but also represents a space where effective marketing efforts can be undertaken, from the provision of information to promotion of companies and their products, and management of relations with prospective customers. A business model is defined in the article as an abstract term referring to an undertaking, its methods and manners of operation and sources of value generated by that undertaking. The existing classifications of online business models can be summarised in one typology consisting of ten core models. In practice many enterprises in the electronic economy use elements from more than one model. Social media are usually defined as undertakings which rely on the Advertising model. Frequently, however, they also draw on elements from the Network and Infomediary models. The purpose of this paper is to locate social networking solutions within the classification of business models on the Internet and to present new trends in the electronic economy against this backdrop.

Środowisko wirtualne oferuje nową, dynamiczną przestrzeń do prowadzenia działalności gospodarczej. Ogół działalności biznesowej odbywającej się na rynkach elektronicznych można określić mianem gospodarki elektronicznej. Obejmuje ona swym zakresem nie tylko wirtualne miejsce do dokonywania transakcji, ale także stanowi przestrzeń skutecznego marketingu dla firmy, począwszy od informacji aż po promocję firmy i jej produktów oraz utrzymywanie relacji z potencjalnymi klientami. Model biznesowy jest tu rozumiany jako abstrakcyjne określenie przedsięwzięcia, sposobów i metod jego działania oraz źródeł generowania wartości przez to przedsięwzięcie. Istniejące klasyfikacje modeli biznesowych w Internecie sprowadzić można do jednej typologii zawierającej dziesięć modeli głównych. W praktyce wiele przedsięwzięć w gospodarce elektronicznej wykorzystuje elementy z więcej niż jednego modelu. Media społecznościowe z reguły definiowane są jako przedsięwzięcia wykorzystujące model reklamowy. Często korzystają także z elementów modelu sieciowego i infomediacyjnego. Celem artykułu jest umiejscowienie rozwiązań społecznościowych w klasyfikacji modeli biznesowych funkcjonujących w Internecie oraz prezentacja na tym tle nowych trendów w gospodarce elektronicznej.